Method of pedotransfer modeling of soil moisture supply on sloping lands - Belolipsky, V. O.; Laktionova, T. M.; Polulyakh, M. M. (AgroChemistry and Soil Science, 2021)
The purpose of the article is to describe a method for developing pedotransfer models for predicting soil moisture supply within an agricultural landscape on sloping, eroded lands (in Luhansk region) during different stages of the growing season of agricultural crops. The models are based on calculating the coefficient of moisture deficit in the soil or the coefficient of moisture content (for April) — predictors. The following factors were used as predictors in pedotransfer models: the amount of precipitation during the growing season; soil moisture coefficient in April; Hydrothermal coefficient; coefficient of normalized atmospheric precipitation for the cold period; humus content in the layer 0-20 cm; soil washout coefficient; the bulk density of the soil in the layer 0-20 cm; height on the profile; coefficient of protective action of forest belts; coefficient of agrobackground. The initial information is a systematized set of data — hydrological characteristics of agricultural landscapes and soil properties, partially published by the authors earlier in the guidelines. The method of pedotransfer modeling of soil moisture supply on slope lands includes sequential mathematical and statistical analysis (using GIS technologies) according to the following thematic stages: (i) selection of factors affecting soil moisture supply as predictors of pedotransfer models; (ii) cluster analysis of the efficiency of soil moisture supply factors in the catchments of the agricultural landscape; (iii) development of pedotransfer models of soil moisture supply based on fragments of the growing season of crops by constructing regression equations and assessing the adequacy of the models by statistical criteria. The models are developed taking into account the phases (periods) of organogenesis of crops and the sequence of agrotechnical measures in the soil protection system of agriculture. It was found that among the studied factors, the most influential factor in predicting the soil moisture supply in any period is the agrophone factor, the share of which in different models ranges from 46 to 89 %. At the same time, the share of the influence of the natural factor of humidification — the Hydrothermal coefficient, is limited to the range of 10–17 %. It is shown that according to the results of predicting the moisture deficit in the soil, the territory of the agricultural landscape can be conditionally divided into working areas for the development of a differentiated system of practical agrotechnical measures to correct the supply of plants with productive moisture.